Screening Women in Glasgow: Comparing uptake across cancer screening programmes at an individual patient level. (2018) - Papworth, Richard; McCowan, Colin; McSkimming, Paula; Kotzur, Marie; McConnachie, Alex; MacDonald, Sara; Wyke, Sally; Crighton, Emilia; Weller, David; Campbell, Christine; Steele, Robert JC; Robb, Katie
No abstract available